A new species of Pareiorhaphis (Siluriformes: Loricariidae) from the headwaters of the Arroio Garapiá, coastal drainage of Rio Grande do Sul state, Brazil - Pereira, Edson H. L.; Lehmann, Pablo A; Schvambach, Lucas J.; Reis, Roberto E. (Zootaxa, 2015)
Pareiorhaphis garapia, new species, is described based on specimens collected in the headwaters of the Arroio Garapiá, Rio Maquiné basin, a coastal drainage of Rio Grande do Sul State, southern Brazil. The new species is distinguished from all other Pareiorhaphis species in having the nuchal plate covered by thick skin, the exposed posterior process of the cleithrum comparatively narrow, and the last segment of the preopercular ramus of the latero-sensory canal reduced to an ossified tubule. The absence of a dorsal-fin spinelet, the reduced number of plates in the dorsal and mid-dorsal series of lateral plates, and morphometric traits also distinguish the new species from its congeners. The restricted geographic distribution of P. garapia, endemic to a headwater stream of the Rio Maquiné basin, and the syntopic occurrence of P. nudulus are discussed.